THE IMPACT OF THYROID DYSFUNCTION ON MOOD DISORDERS: A SYSTEMATIC REVIEW WITH NARRATIVE SYNTHESIS - Agnieszka Pocheć; Anastasiia Holoborodko; Ewa Wieczorkiewicz; Patrycja Stępińska; Eliza Garbacz; Bartosz Lautenbach; Dariusz Nędza; Klaudia Wojciech; Anhelina Loputs; Wiktoria Błaszczyk (International Journal of Innovative Technologies in Social Science, 2025)
Background: Thyroid dysfunction is increasingly linked to depressive, anxiety, and cognitive symptoms, yet the mechanisms and long-term implications of these associations remain incompletely understood. Emerging evidence suggests that hormonal imbalance, autoimmunity, and neural pathway alterations jointly contribute to psychiatric manifestations in thyroid dysfunction. Aim: This systematic review with narrative synthesis synthesizes current evidence across epidemiological, clinical, cognitive, and neuroimaging domains to clarify the multidimensional relationship between thyroid function and mood regulation. Methods: A systematic search of PubMed, Scopus, Web of Science, Cochrane Library, and Embase (2010–2025) identified studies evaluating mood, anxiety, cognitive, or neuroimaging outcomes in adults with overt, subclinical, or autoimmune thyroid dysfunction. Eligible designs included randomized trials, cohort and cross-sectional studies, neuroimaging investigations, and systematic reviews. Data were synthesized thematically, and quantitative estimates from high-quality meta-analyses were incorporated where applicable. Risk of bias was assessed using NOS, AXIS, RoB2, and AMSTAR-2 tools. Results: Forty-two studies met inclusion criteria. Thyroid dysfunction was consistently associated with increased depressive and anxiety symptoms, cognitive complaints, and alterations in hippocampal and prefrontal circuitry. Autoimmune thyroid disease was consistently associated with depressive, anxiety, and cognitive symptoms. A subset of patients continued to experience psychological symptoms despite biochemical normalization. Meta-analytic evidence indicated a modest but significant increase in depression risk in subclinical hypothyroidism, particularly among younger adults. Conclusion: Thyroid dysfunction affects mental health through intertwined hormonal, immune, and neural mechanisms. Persistent symptoms highlight the need for integrated endocrine-psychiatric care and standardized diagnostic approaches.